Analysis of inorganic ions and trace metals (elements) in Singapore precipitation and reservoir using ICP-OES and IC. - Tan, Jocelyn Yi Ching. (2010)
The concentrations of major inorganic ions (Na+, K+, Mg2+, Ca2+, NH4+, F-, Cl-, NO3-, SO42-), 12 trace metals/elements and selected elements (As, Al, Cd, Cr, Co, Cu, Fe, Mn, Pb, Zn, Ni and V) in precipitation collected from 75 rainwater samples at three different locations in Singapore from December 2009 to March 2010 were reported. These samples were subjected to chemical analysis by ion chromatography (IC) and inductively coupled plasma optical emission spectrometry (ICP-OES), where inorganic ions and elements were measured respectively. The dominant ions were Ca2+, Na+, Cl- while trace metals Al, Cu and element Fe were present in abundance. The pH range from 3.41 to 7.53 where different rainwater acidity was observed for different locations. The enrichment factor was calculated to distinguish and identify the sources of origin. Factor analysis was also calculated to further categorize common natural and anthropogenic sources. The scavenging of elements by precipitation and their chemical composition present was influenced by local meteorological conditions.